ANALISIS PERAN GURU SEBAGAI KONSELOR DALAM MENGATASI MASALAH EMOSIONAL PADA ANAK DI TK KEMALA BHAYANGKARI 55 SURAKARTA - Lailatul Mucharromah, Rosyida; Feri Faila Sufa; M. Hery Yuli Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotional issues in early childhood-such as tantrums, aggressive behavior, anxiety, and difficulty regulating emotions require appropriate management to prevent them from hindering a child's socio emotional development. In the context of Early Childhood Education (ECE), teachers act not only as educators but also as counselors who provide guidance to children in overcoming emotional challenges. This study aims to describe the teacher's role as a counselor and the strategies implemented to address emotional issues among young children at TK Kemala Bhayangkari 55 Surakarta. The study employs a descriptive qualitative approach using a case study strategy. The research subjects consisted of one "Class A" teacher as the primary informant, along with the school principal and two parents as supporting informants. Data were collected through observation, semi-structured interviews, and documentation. Data validity was verified using source and technique triangulation, while data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the teacher has fulfilled the role of counselor through preventive, curative, and developmental functions. Strategies implemented include empathetic communication, positive reinforcement, conflict mediation, building warm relationships with children, fostering cooperative play habits, and collaborating with parents. These strategies assist children in recognizing, managing, and controlling their emotions, enhancing social interaction skills, and creating a safe and conducive learning environment. Thus, the teacher acting as a counselor plays a strategic role in supporting the emotional development of young children.